Kualifikasi Agen Perubahan dalam Mewujudkan Sekolah Adaptif terhadap Transformasi Pendidikan di SMPN 2 Padang Panjang - Habib Bintang Anugrah (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This study aims to analyze the qualifications of change agents in realizing an adaptive school toward educational transformation at SMPN 2 Padang Panjang. A qualitative approach was employed using in-depth interviews with five informants, consisting of the principal, a guidance and counseling teacher, an Islamic education teacher, and two students. The findings reveal that the principal acts as the main driver of transformation by implementing participatory and innovative leadership to build an adaptive school culture. The guidance and counseling teacher functions as a social and emotional mediator who helps students understand the meaning of change while fostering reflective behavior and learning responsibility. The Islamic education teacher plays a crucial role in instilling spiritual and moral values contextualized to modern realities through value clarification–based learning. Meanwhile, students demonstrate increased awareness, autonomy, and engagement, marking a shift from teacher- centered to student-centered learning. The synergy between visionary leadership, humanistic counseling services, value-based education, and active student participation serves as the foundation for developing an adaptive school environment. These findings emphasize that the success of educational transformation is not solely determined by structural policies but by the capacity of each school actor to function as a reflective, collaborative, and forward-oriented change agent committed to continuous development.